Impact of ex-situ annealing on strain and composition of MBE grown GeSn. (8th September 2020) - Jia, Hui; Jurczak, Pamela; Yang, Junjie; Tang, Mingchu; Li, Keshuang; Deng, Huiwen; Dang, Manyu; Chen, Siming; Liu, Huiyun
Abstract: The application of GeSn is extended to semiconductor lasers thanks to its band engineering via Sn composition and strain manipulation. As one of the strain engineering methods, thermal annealing, however, is not yet being widely adopted by the majority due to the thermal instability it induces. The thermal stability of GeSn is highly sensitive to initial material conditions, consequently thorough investigations are still demanded with different purposes. A detailed investigation on the thermal annealing effects of thick GeSn layers with a nominal 8% Sn grown on Ge-buffered Si (001) substrate by molecular beam epitaxy is presented here. Atomic force microscopy and high-resolution x-ray diffraction were used to trace the change of GeSn surface morphology and the strain relaxation after annealing. It is confirmed that the tetragonal compressive strain in GeSn, which is a proven detriment to the realisation of direct-bandgap material, can be relaxed by 90% while improving crystal quality, e.g. reduced surface roughness by appropriate annealing conditions. These findings reveal the potential of annealed GeSn to serve as a much thinner (750 nm), better lattice-matched to GeSn active layer and highly strain-relaxed platform to grow GeSn on compared to the thick Ge or the compositional-graded (Si)GeSn buffer layers, which are complicated and time-consuming in growth procedures and also securing an easier approach.